Nutrient utilization, rumen fermentation characteristics and ciliate protozoa population in sheep and goats under stall feeding - SANTRA, A; KARIM, S A (The Indian Journal of Animal Sciences, 2014)
A study was conducted on stall fed sheep and goats to assess their relative nutrient utilization, rumen fermentation characteristics and ciliate protozoa count under ad lib. feeding regimen. Dry matter intake (DMI) was higher (P<0.01) in sheep while digestibility of nutrients particularly cell-wall constituents were higher in goats. Both sheep and goats were in positive nitrogen (N) balance whereas the per cent N retention was higher in goats (24.7 %) than that in sheep (19.6 %). The pH of strained rumen liquor (SRL) decreased from 0 to 6 hr post-feeding while the total VFA concentration followed a reverse trend. Total N content ofSRL was higher in goats while NH -N concentration was higher in sheep. The rumen ciliate protozoa of sheep were B-type population mainly due the presence of Epidinium species and absence of Polyplastron multivesiculatum whereas goats had A-type population. Total protozoal count was higher in goats than that in sheep while the count was lowest just before feeding with abrupt increase in number of holotrich and spirotrichs at 2 hr post-feeding. The results indicated that although DMI was lower in goats than sheep, their better digestive efficiency particularly cell-wall constituents was reflected in similar plane of nutrition between the two species. The lower rumen NH)-N value in goats is indicative of their efficient utilization of dietary protein. Moreover, better digestibility of cell-wall constituents in goats was ascribed to their higher rumen protozoal count.